2015
DOI: 10.1177/0022343315580145
|View full text |Cite
|
Sign up to set email alerts
|

Land grievances and the mobilization of electoral violence

Abstract: Recent studies have asked why elites resort to violence, yet many overlook the process and dynamics of mobilizing violence. How do politicians convince their supporters to fight? This article argues that in multi-ethnic and democratizing societies where land and property rights are weak and politicized, land grievances can provide leaders with a powerful tool to organize electoral violence. We develop a theory to show how land grievances can give rise to violent mobilization when leaders frame elections as a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(63 citation statements)
references
References 40 publications
2
59
1
1
Order By: Relevance
“…Recent studies have shown how the ambiguous and contested nature of property rights regimes has enabled political elites to mobilize supporters by playing upon the land issue-particularly through electoral politics (Boone, 2009;Boone, 2014;Klaus & Mitchell, 2015;Onoma, 2010). In a context where claims to land are easily disputed owing to a weak and/or insecure property rights regime, land becomes a major cleavage issue pitting locals against migrants.…”
Section: Insecure and Unenforceable Property Rights Regimesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown how the ambiguous and contested nature of property rights regimes has enabled political elites to mobilize supporters by playing upon the land issue-particularly through electoral politics (Boone, 2009;Boone, 2014;Klaus & Mitchell, 2015;Onoma, 2010). In a context where claims to land are easily disputed owing to a weak and/or insecure property rights regime, land becomes a major cleavage issue pitting locals against migrants.…”
Section: Insecure and Unenforceable Property Rights Regimesmentioning
confidence: 99%
“…In a context where claims to land are easily disputed owing to a weak and/or insecure property rights regime, land becomes a major cleavage issue pitting locals against migrants. And yet as comparative research on SoS conflicts and elections reveals, politicians are much less likely to attempt to instrumentalize the issue of property rights when there is mutual agreement around the norms and practices embodied in the property rights regime operating within local communities (Côté & Mitchell, 2015;Klaus & Mitchell, 2015). In contexts where land rights and ownership have been highly regulated and controlled by local traditional authorities (i.e.…”
Section: Insecure and Unenforceable Property Rights Regimesmentioning
confidence: 99%
“…Although the 2015 elections were peaceful, issues underpinning the social turmoil that led to conflict in the recent past -namely land grievances and identity politics -have not yet been addressed meaningfully and continue to pose challenges to Côte d'Ivoire's democratic development (Klaus and Mitchell 2015;Whitaker 2015). Tests for Côte d'Ivoire's democratic consolidation continue into the future, when election years might occur during years of economic decline or stagnation, which would create a starker trade-off for incumbents between electoral defeat and free and fair elections.…”
Section: Resultsmentioning
confidence: 99%
“…Elections in democratizing regimes have been found to be more vulnerable to violence than those held in either fully democratic or fully authoritarian states (Klaus & Mitchell, 2015;Mochtak, 2016). There are several possible reasons for this: the fragility of democratic institutions in countries 4 moving towards democracy means that democratic governance may not be entirely accepted by all actors in the electoral arena as the only game in town.…”
Section: Introductionmentioning
confidence: 99%